Unveiling Students' Refractive Thinking Process Who Use a Single Strategy in Decision Making - Prayitno, Anton; Widayanti, Febi Dwi (Edumatika, 2024)
The thinking process characterized by reflective thinking towards critical thinking to produce a decision is called the refractive thinking process. However, how the refractive thinking process occurs in the subject needs to be revealed. This study aims to reveal the refractive thinking process in subjects who use a single strategy in decision making. This study is a qualitative approach involving 25 mathematics education students from two universities in Malang, East Java, Indonesia. Each student was given a test on the problem of ordering cities based on the level of dependence on the central government from lowest to highest. The decision to order cities was based on local revenues data that varied between cities and unstable from year to year. In this study, the researcher only analyzed the refractive thinking process of one subject who used a single strategy in decision making. The subject was asked to think aloud. The results showed that students who carried out the refractive thinking process with a single strategy only needed one alternative solution to make a decision, namely by summing up the contributions of each city per year. The subject only identified the comparison of the amount and increase in the contribution of each city as a consideration for making a decision.